Human stabilization of river flows is linked with fish invasions across the USA - Lise Comte; Theodore Grantham; Albert Ruhi (Global Ecology and Biogeography, 2021)
Aim River flow regimes are changing globally as a consequence of human use of freshwater resources. Additionally, rivers are among the most invaded ecosystems. Invasion biology predicts that the establishment and spread of non‐native species might be favoured both by new environmental regimes (niche opportunities) and by human‐mediated dispersal (propagule pressure). Here, we expand on past research by asking whether these two mechanisms act in isolation or whether they interact to facilitate the spread of non‐natives. Location Conterminous USA. Time period 1987–2016. Major taxa studied Freshwater fishes. Methods First, we examined the geography of riverine fish invasions across 1,148 watersheds spanning the conterminous USA. We focused on species richness and the life‐history strategies of non‐native (both translocated and exotic) relative to native species pools. Second, we quantified flow regime alteration as the deviation between observed and expected contemporary flow regimes, using a combination of spectral analyses on long‐term discharge data and random forest models. We focused on two biologically relevant facets of the flow regime: flow variability and flow seasonality. We also estimated metrics of propagule pressure: recreational fishing pressure and socioeconomic activity. We then compared the strength of evidence associating riverine fish invasions with flow alteration, propagule pressure, and interactions between the two mechanisms. Results We found that alteration of flow variability and seasonality is widespread across the conterminous U.S. rivers, and has favoured invasions by filtering specific life‐history strategies. Importantly, high levels of flow stabilization and propagule pressure interacted: where co‐occurring, these two drivers were associated with higher fish invadedness levels than expected based on their individual effects. Main conclusions Our results underscore the need to consider different drivers of invasion concurrently. Otherwise, important synergistic interactions might be missed that could explain (and guide management strategies to mitigate) the high levels of invasion in fresh waters.